Biochemical properties of oyster mushroom(Pleaurotus florida) grown on different agricultural straw at North Gujarat condition. - Shinde, Manisha; Prajapati, Priyanka; Patel, J. S.; Chandaragi, M. K. (Mushroom Research, 2025)
Mushrooms provide numerous benefits to humans. One important attribute is as a food source as they are rich in essential proteins, carbohydrates, amino acids and vitamins. So the experiment was so conducted to know biochemical properties of oyster mushroom (Pleurotus florida) which was grown different agricultural straw during the year 2022-23. Among them, highest crude protein content (24.15 %) and total soluble sugar (44.19 mg/g) were observed in the mustard straw substrate. While, groundnut shell recorded the highest moisture content (92.67 %). While, in the case of phenol content and antioxidant activity (DPPH) were recorded highest in wheat straw (1.81 mg/g) and (42.94 mg/g), respectively